2012
DOI: 10.1038/nature11225
|View full text |Cite
|
Sign up to set email alerts
|

Dietary-fat-induced taurocholic acid promotes pathobiont expansion and colitis in Il10−/− mice

Abstract: The composite human microbiome of Western populations has likely changed over the past century, brought on by new environmental triggers that often have a negative impact on human health 1 . Here we show that consumption of a diet high in saturated (milk derived)-fat (MF), but not polyunsaturated (safflower oil)-fat (PUFA), changes the conditions for microbial assemblage and promotes expansion of a low abundance, sulfite-reducing pathobiont, Bilophila wadsworthia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

63
1,291
5
18

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,608 publications
(1,377 citation statements)
references
References 25 publications
63
1,291
5
18
Order By: Relevance
“…49 Consumption of taurine and TCA has been shown recently to cause a bloom in the sulfidogenic bacterium, Bilophila wadsworthia, resulting in colitis in the IL10-/-mouse model. 50 Consequences of bile salt hydrolysis for the mammalian host Cardiovascular disease is responsible for 16.7 million deaths worldwide and is the leading cause of mortality and morbidity worldwide. 51 There is a clear link between serum cholesterol and cardiovascular disease, particularly coronary artery disease (CAD).…”
Section: A Microbial View Of Bile Salt Hydrolysismentioning
confidence: 99%
“…49 Consumption of taurine and TCA has been shown recently to cause a bloom in the sulfidogenic bacterium, Bilophila wadsworthia, resulting in colitis in the IL10-/-mouse model. 50 Consequences of bile salt hydrolysis for the mammalian host Cardiovascular disease is responsible for 16.7 million deaths worldwide and is the leading cause of mortality and morbidity worldwide. 51 There is a clear link between serum cholesterol and cardiovascular disease, particularly coronary artery disease (CAD).…”
Section: A Microbial View Of Bile Salt Hydrolysismentioning
confidence: 99%
“…Early-life gut microbial populations play a critical role in the development of the nervous system and the immune response and have been shown to affect behaviors such as anxiety and motor control into adulthood (3)(4)(5)(6). Current findings also identified a role for the gut microbiome in the development of gastrointestinal diseases, such as ulcerative colitis and irritable bowel syndrome (7,8), in metabolic pathologies such as insulin resistance (9) and obesity (10,11) and in neurological disorders such as autism (12), Parkinson disease (13), and Alzheimer disease (14). Due to evidence linking the gut microbiome with human health and disease, it has been suggested that nurturing the development of a healthy patient/microbial ''superorganism'' is a cornerstone in the future of medicine (15,16).…”
Section: Introductionmentioning
confidence: 93%
“…Dextran sodium sulfate (DSS) treatment of MF-fed SPF C57BL/6 mice induced more severe colitis than in their LF and PUFA fed counterparts, as well as consistent observations of B. wadsworthia. 52 In mono-associated germ-free Il10 ¡/¡ mice, colonization of B. wadsworthia could only be obtained in MF fed mice, and abundance was greater mainly in the mucosa. B. wadsworthia grown in culture medium was selectively stimulated by gallbladder bile from MF-fed mice.…”
Section: Diet and Gut Microbial Respiration Of Taurinementioning
confidence: 99%